2017
DOI: 10.1002/pros.23407
|View full text |Cite
|
Sign up to set email alerts
|

Reduced number of CD169+ macrophages in pre‐metastatic regional lymph nodes is associated with subsequent metastatic disease in an animal model and with poor outcome in prostate cancer patients

Abstract: BackgroundTumor‐derived antigens are captured by CD169+ (SIGLEC1+) sinus macrophages in regional lymph nodes (LNs), and are presented to effector cells inducing an anti‐tumor immune response. Reduced CD169 expression in pre‐metastatic regional LNs is associated with subsequent metastatic disease and a poor outcome in several tumor types, but if this is the case in prostate cancer has not been explored.MethodsCD169 expression was measured with immunohistochemistry in metastasis‐free regional LNs from 109 prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 38 publications
4
42
0
Order By: Relevance
“…Network enrichment analysis enabled clarification on this matter as we found that growth-and immune signaling pathways are specifically up-regulated in SN Tregs, suggesting an active role of these cells in the SN of MIBC patients. This finding is in congruence with a recent report of pre-metastatic, immunosuppressive, changes in regional lymph nodes of prostate cancer, demonstrated in a mouse model (259) and is also in line with studies of other malignancies demonstrating a suppressive impact and increased frequency of Tregs in the SN (260,261).…”
Section: Il-16 Processing In Sentinel Node Tregs Is a Factor In Tumorsupporting
confidence: 92%
“…Network enrichment analysis enabled clarification on this matter as we found that growth-and immune signaling pathways are specifically up-regulated in SN Tregs, suggesting an active role of these cells in the SN of MIBC patients. This finding is in congruence with a recent report of pre-metastatic, immunosuppressive, changes in regional lymph nodes of prostate cancer, demonstrated in a mouse model (259) and is also in line with studies of other malignancies demonstrating a suppressive impact and increased frequency of Tregs in the SN (260,261).…”
Section: Il-16 Processing In Sentinel Node Tregs Is a Factor In Tumorsupporting
confidence: 92%
“…Despite that we found no literature evidence of the downregulation of expression in LUAD for all component genes in the CAMs pathway, the tumor suppressor roles of SIGLEC1 and CADM1 human cancers were explored in previous research. The study conducted by Strömvall et al confirmed that reduced expression of SIGLEC1 in metastasis-free regional lymph nodes was responsible for the inhibited antitumor immune response ( 61 ). CADM1, a membrane-spanning glycoprotein that participates in the process of attenuating cell proliferation and activating cell apoptosis, was downregulated in various cancers such as breast, prostate, pancreatic and hepatocellular cancer ( 62 ).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, we detected lower levels of Csf1/Csfr1 , Clec1b , Osm , Tnfsf11 in MLL-LNs that could result in decreased numbers of antigen presenting cells and impaired function of high endothelial venules [ 11 , 26 30 ]. The number of SIGLEC1 + (CD169) sinus macrophages were also reduced in MLL-LNs [ 31 ] further suggesting decreased antigen-presentation in pre-metastatic LNs. Such changes could possibly precondition the LNs for subsequent metastatic growth (microscopically evident 4 days later in this experimental model).…”
Section: Discussionmentioning
confidence: 99%
“…The question whether particularly aggressive human prostate tumors can create pre-metastatic changes in regional LNs, and if so at what stage of tumor development, is largely unknown. However, some studies of pre-metastatic LNs suggest that the levels of VEGFR1[ 51 , 52 ], IL30 [ 53 ], and CD169 [ 31 ] are related to disease progression after prostatectomy. Tumor-free LNs from prostate cancer patients contained more CD68 + and pSTAT-3 + macrophages than LNs from individuals without prostate cancer [ 54 ].…”
Section: Discussionmentioning
confidence: 99%